Assessing the conservation value of cemeteries to urban biota worldwide - Yuval Itescu; Jonathan M. Jeschke (Conservation Biology, 2024)
Cemeteries are key urban green spaces with multifaceted societal and ecological importance. Their biodiversity is shaped by unique environmental and cultural factors. They can potentially protect rare and endangered species, yet their conservation value compared with other urban green spaces remains largely unexplored. We sought to fill this gap by systematically reviewing literature to investigate the conservation value of cemeteries relative to other urban green spaces (botanical gardens, institutional premises, natural remnants, and parks) by comparing species richness and proportions of native and unique species. We analyzed data from 70 papers covering 50 cities in 27 countries with linear and binomial mixed‐effects models at both site and city level. Cemetery conservation value was similar to urban parks, except for the proportion of unique species, for which parks had significantly higher proportions (21.9% vs. 14.2%, p p p = 0.034) and proportions comparable to parks and natural remnants ( p > 0.05). They also had similar or higher values than institutional premises in species richness and unique species proportions ( p > 0.05) and a higher site‐level proportion of native species ( p p